Balancing Partial Ionic and Electronic Transport for Optimized Cathode Utilization of High‐Voltage LiMn2O4/Li3InCl6 Solid‐State Batteries. Issue 4 (8th February 2023) - Hendriks, Theodoor A.; Lange, Martin A.; Kiens, Ellen M.; Baeumer, Christoph; Zeier, Wolfgang G.
Abstract: Their suggested stability towards high‐voltage cathode materials makes halide‐based solid electrolytes currently an interesting class of ionic conductors for solid‐state batteries. Especially the LiMn2 O4 spinel cathode active material is of interest due to its slightly higher nominal voltage and more resilience to overcharging compared to LiCoO2 and LiNi x Mn y Co z O2 cathodes. Typically, a standard ratio of active material to solid electrolyte is used in composites for solid‐state batteries. However, for ideal transport properties, and thus to achieve balanced and optimal partial‐conductivities, this ratio needs to be re‐optimized each time the material basis is changed. In this work, we show transport in the composite measured through both DC polarization as well as transmission line modeling of the impedance spectra. By balancing the partial transport parameters of the composite, an optimum capacity of the solid‐state batteries is achieved. This work shows characterization and optimization of transport is required for unlocking the full potential of solid‐state batteries. Abstract : Balanced ions/electrons transport : Optimal performance and capacity in solid‐state batteries with a composite cathode can only be achieved when the transport within is optimized to be balanced. This work shows that both DC polarization and transmission line modelling can be employed to measure partial conductivities and with it optimize the composite to achieve balanced transport.